Impact of board of directors’ characteristics on accrual and real earnings management among Jordanian listed firms: conceptual paper - Al Nohood, Saddam; Abdul Hamid, Mohamad; Abdul Latiff, Ahmed Razman (Human Resource Management Academic Research Society, 2024)
This study aims to develop a theoretical framework that paves the way for future empirical research measuring the impact of boards of directors through independence, activity (number of meetings), financial expertise, and foreign directors on the magnitude of earnings management, both accrual and real. The current study proposes that the sample of the coming empirical study be Jordanian industrial and service firms listed on the Amman Stock Exchange during the period from 2014 to 2019, given the importance of these companies and their significant contribution to national income. The choice of such a study period is important because it is likely to contribute to measuring the effectiveness of boards of directors during two important phases in the life of Jordanian corporate governance: the first is the “comply or explain” phase according to the Corporate Governance Code that entered into force in 2009, and the second is the “enforced” phase according to its latest revisions in 2017. Additionally, the importance of the study stems from the idea of giving Jordanian companies more time to adapt to corporate governance, in line with the claim that the quality of corporate governance matures over time. Further, choosing real earnings management will contribute to the earnings management literature, given the scarcity of previous research conducted on this issue in Jordan. The results of future empirical studies are expected to have implications for Jordanian legislators and policy-makers by distinguishing between good and weak corporate governance tools.